HEALTH FACILITY FACTORS INFLUENCING MALE INVOLVEMENT IN ANTENATAL CARE AMONG CLIENTS ATTENDING ANTENATAL CLINIC AT NEBBI GENERAL HOSPITAL, NEBBI DISTRICT A CROSS-SECTIONAL STUDY. - Adero , Teddy; Atim , Miria (Student’s Journal of Health Research Africa, 2024)
Background Antenatal care (ANC) is crucial for maternal and fetal health, yet male involvement in ANC remains low globally. Despite efforts to encourage male participation, studies indicate low levels of involvement across Africa, including Uganda. This study aims to identify factors influencing male involvement in ANC at Nebbi General Hospital. Methods The study employed a cross-sectional quantitative approach using purposive sampling to collect data from pregnant women and their partners attending the antenatal clinic, with a final sample size of 37 participants, and data analysis conducted using SPSS version 20.0 Results and discussions There was a 100% response rate with 37 participants. The study revealed that distance to the facility, discussion of antenatal care with health workers, and comfort with health workers’ gender were key determinants of male involvement. Conclusion Various health facility factors significantly influence male participation in antenatal care (ANC), affecting maternal and child health outcomes. Recommendation To improve male involvement in ANC, hospitals should provide flexible clinic hours, especially for working men. District health officers should address health facility factors and train health workers to effectively engage with male partners. Nursing implications Nurses should educate expectant mothers and their male partners on the importance of male involvement in ANC and its impact on pregnancy outcomes, advocating for flexible clinic hours to accommodate diverse backgrounds.